Antifungal effects of Curcuma longa L. essential oil against pathogenic strains isolated from indoor air - Gámez Espinosa, Erasmo Junior (2020)
Curcuma longa L. essential oil can be considered a natural product with strong antifungal activity due to the fungicidal and fungistatic effect. It can be used for the aeromycological control of premises where food is prepared. It is important to monitor air quality in food production facilities to achieve safe food. The objective of this work was to evaluate the antifungal activity of C. longa essential oil on potentially pathogenic and biodegradable strains isolated from the indoor of the food industry. A suspension of 106 spores/mL of the strains Aspergillus flavus, Penicillium brevicompactum and Cladosporium cladosporioides was prepared. Two natural biocides (C. longa essential oil and Cuban propolis) and two synthetic ones (antiseptic detergent and Tween 20) at different concentrations (0, 0.001, 0.1 and 1.0% v/v) were evaluated. The superficial growth of the mycelium (cm) and the germination inhibition (%) were the response variables. In addition, the minimum inhibitory concentration (MIC) of EO was determined by radial growth total inhibition (IRG) and partial sporulation inhibition (PIS). A. flavus colony diameter was decrease inversely proportional to the concentrations, and at 1% v/v it reduced more than three times its diameter, being selected as MIC since it caused IRG and PIS. Germination inhibition of the spores of the three strains was observed in relation directly proportional to the concentration of the four biocides. All spores with values similar to antiseptic detergent were inhibited by the essential oil at MIC (1%) between 41 and 55%